1877 Terr. of Dakota Rev. Codes 798, Penal Code, ch. 39, § 495 - (:unkn) unknown (General Publisher, 1877)
Every person who willfully discharges any species of firearms, air-gun or other weapon, or throws any other missile in any public place, or in any place where there is any person to be endangered thereby, although no injury to any person shall ensue, is guilty of a misdemeanor.
--
Keywords: DISCHARGE